2001
DOI: 10.1021/la001302h
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy Study of Immobilization Processes for Heavy Metals in Calcium Silicate Hydrates. 2. Zinc

Abstract: Tricalcium silicate (C3S), the major phase of cement-based materials, contains naturally a few hundred parts per million of heavy metals. An X-ray absorption spectroscopy (XAS) study at the Zn K-edge has been carried out to elucidate the binding mechanisms of Zn by calcium silicate hydrates, which is important to predict the long-term behavior of Zn. At low concentration, under the threshold of precipitation of the oxide, oxy hydroxide, and calcium zinc hydroxide, no retardation of the hydration of the C3S has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…Also, the Zn ion can be incorporated into CSH compounds, which is the major phase in hydrated cement (Rose et al 2001). Therefore, if the TCLP solution is buffered enough by the S/S agents, effective Zn immobilization should be expected.…”
Section: Tclp Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the Zn ion can be incorporated into CSH compounds, which is the major phase in hydrated cement (Rose et al 2001). Therefore, if the TCLP solution is buffered enough by the S/S agents, effective Zn immobilization should be expected.…”
Section: Tclp Resultsmentioning
confidence: 99%
“…The Zn substitution occurs either by replacement of Ca 2? or by direct linkage to the end of the silicate chains through Zn-O-Si bonds (Moulin et al 1999;Rose et al 2001). Moreover, the formation of Zn 6 Al 2 (OH) 16 CO 3 Á4H 2 O and CaO[Zn(OH) 2 ]Á2H 2 O have been reported when the Zn(OH) 2 was blended with PC (Qiao et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectra of Group 1 compounds were very similar and included all of the weakly-complexed Zn species: Znsalts, the carboxylates Zn-acetate, and Zn-succinate (both pH), and the amino acids Zn-Pro and Zn-Ala (pH 5.6). The differences between the spectra of individual or groups of reference compounds are attributed to variations detected by XANES in the electronic transitions from 1s to unoccupied 4p molecular orbitals which constitute the first coordination sphere of Zn (Rose et al 2001).…”
Section: Zinc Concentration Ph and Weight Of Plant Tissues And Xylemmentioning
confidence: 99%
“…The application of XAS to complex matrices in relation to environmental fate and behavior of contaminants is still relatively rare, but it has been employed in a limited number of studies of the speciation of metals in cement pastes, including chromium [9], cobalt [10], copper [11], lead [12], neodymium [13], selenium [14], tin [15], uranium [16] and zinc [17], as well as nickel [18][19][20]. Apart from Rinehart et al [9], who examined the oxidation state of chromium in a s/s contaminated soil and showed that this was not affected by S/S, and Hsaio et al [11], who indicated that S/S respeciated CuCl2 and reduced forms of copper in municipal waste incinerator air pollution control residues to Cu(OH)2, other studies have all prepared hydrated cement pastes by mixing pure solutions of soluble metal salts with cement powder.…”
Section: Introductionmentioning
confidence: 99%